2019
DOI: 10.1038/s41550-019-0768-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency gravity waves in blue supergiants revealed by high-precision space photometry

Abstract: Almost all massive stars explode as supernovae and form a black hole or neutron star. The remnant mass and the impact of the chemical yield on subsequent star formation and galactic evolution strongly depend on the internal physics of the progenitor star, which is currently not well understood. The theoretical uncertainties of stellar interiors accumulate with stellar age, which is particularly pertinent for the blue supergiant phase. Stellar oscillations represent a unique method of probing stellar interiors,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
156
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 43 publications
(56 reference statements)
18
156
0
Order By: Relevance
“…With the advent of high-precision space-borne photometry, it has also been found that a number of massive OB stars display elevated signal levels at low frequencies, aka "red noise", in their photometric times series (e.g. Blomme et al 2011;Ramiaramanantsoa et al 2018;Rauw et al 2019;Bowman et al 2019Bowman et al , 2020. Our γ Cas stars are no exception, showing that these stars fit the typical behaviour seen for stars of similar spectral types.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…With the advent of high-precision space-borne photometry, it has also been found that a number of massive OB stars display elevated signal levels at low frequencies, aka "red noise", in their photometric times series (e.g. Blomme et al 2011;Ramiaramanantsoa et al 2018;Rauw et al 2019;Bowman et al 2019Bowman et al , 2020. Our γ Cas stars are no exception, showing that these stars fit the typical behaviour seen for stars of similar spectral types.…”
Section: Discussionsupporting
confidence: 61%
“…• Red noise: A gradual increase in periodogram amplitudes can be seen towards the lowest frequencies, especially in HD 45314, once the lightcurve has been detrended and cleaned from its main periods. This so-called "red noise" actually is stellar in origin, rather than instrumental, as its presence has been reported in several massive stars (Blomme et al 2011;Rauw et al 2019;Bowman et al 2019). Subsection 3.1.1 provides further details on the properties of the red noise in our targets.…”
Section: Types Of Variabilitymentioning
confidence: 78%
“…5.1.2 Simón-Díaz et al 2017), since stars with larger pulsation amplitudes typically show larger macroturbulence (Bowman et al 2020). We also note that Rivinius et al (2020) demonstrate variability caused by nonradial gravity-mode pulsations using SMEI and TESS photometry, with such low-frequency photometric variability being common among massive stars (Bowman et al 2019).…”
Section: Medium-term Variability Of the Narrow-lined Primarymentioning
confidence: 52%
“…Saio, Georgy & Meynet (2013) suggest to distinguish between the two BSG types with radial pulsations (e.g. Bowman et al 2019) in addition to the CNO surface enrichment, i.e. BSG type II exhibits radial pulsations.…”
Section: Discussionmentioning
confidence: 99%